Thermal utilization of fingermillet [Eleusine coracana (L.) Gaertn.] cultivars under different sowing dates - Swain, S R; Patra, B; Nayak, J K; Mallick, S; Audhya, T; Nayak, A N; Mishra, Alisha; Nayak, Susmita (Plant Science Today, 2026)
A field study was carried out at the Agricultural Research Station (ARS), Binjhagiri, Chhatabar, SOADU, Bhubaneswar, during the kharif season. The experiment consisted of 3 dates of sowing with 15-day interval allocated to the main plots and 4 finger millet varieties i.e., Arjuna, Kalua, Bhairabi, Shreeratna in sub plots under split-plot design with 3 replications. The 24 June sown finger millet crop showed minimum days for achieving phenology, robust growth with a higher leaf area index (LAI) (4.55) at 60 DAS while maximum number of tillers per hill (9.3) was recorded in 24 July sown crop in 90 DAS. The 24 June sown crop gave maximum grain yield (2193 kg/ha), straw yield (3672 kg/ha), total uptake (41.9, 11.1, 66.7 N, P2O5, K2O kg/ha), GDD (2125.4 oC day), net return (₹57230/ha) and B.C. ratio (1.9). Number of tillers per hill (10.1), LAI (4.42) at 60 DAS and days to maturity (112.4 days) recorded maximum in Shreeratna variety and lowest growth parameters were observed in Kalua variety. Grain yield (2182 kg/ha), straw yield (3587 kg/ha), total uptake, HUE, GDD (2104.9 oC day), net return (₹56585/ha) and B.C ratio (1.8) were significantly higher in Shreeratna variety. The Shreeratna variety sown on 24 June produced significantly maximum yield (2569 kg/ha & 4040 kg/ha in grain and straw respectively), nutrient uptake (47.9, 12.5, 73.6 N, P2O5, K2O kg/ha) and a net return of ₹71737/ha.